Connexin 31.1 degradation requires the Clathrin‐mediated autophagy in NSCLC cell H1299. Issue 1 (11th November 2014) - Zhu, Xingli; Ruan, Zhenchao; Yang, Xiufang; Chu, Kaili; Wu, Hai; Li, Yao; Huang, Yan
Abstract Connexins have relative short half‐lives. Connexin 31.1 (Cx31.1) was newly reported to be down‐regulated in non‐small cell lung cancer cell lines, and displayed tumour‐suppressive properties. However, no reports describing how a cell regulates Cx31.1 level were found. In this study, Cx31.1 was suggested to be degraded through both ubiquitin–proteasome system (UPS) and autophagy. Blockage of UPS with MG‐132 increased Cx31.1 level, but could not inhibit the degradation of Cx31.1 completely. In H1299 cells stably expressing Cx31.1, Cx31.1 reduced when autophagy was induced through starvation or Brefeldin A treatment. Knockdown of autophagy‐related protein ATG5 could increase the cellular level of Cx31.1 both under normal growth condition and starvation‐induced autophagy. Colocalization of Cx31.1 and autophagy marker light chain 3 (LC3) was revealed by immunofluorescence analysis. Coimmunoprecipitation and immunofluorescence showed that Cx31.1 might interact with clathrin heavy chain which was newly reported to regulate autophagic lysosome reformation (ALR) and controls lysosome homoeostasis. When clathrin expression was knockdown by siRNA treatment, the level of Cx31.1 increased prominently both under normal growth condition and starvation‐induced autophagy. Under starvation‐induced autophagy, LC3‐II levels were slightly accumulated with siCla. treatment compared to that of siNC, which could be ascribed to that clathrin knockdown impaired the late stage of autophagy, ALR. Taken together, we found autophagy contributed to Cx31.1 degradation, and clathrin might be involved in the autophagy of Cx31.1.